2017
DOI: 10.3389/fphys.2017.00968
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Muscle Hypertrophy Models Reveals Divergent Gene Transcription Profiles and Points to Translational Regulation of Muscle Growth through Increased mTOR Signaling

Abstract: Skeletal muscle mass is a result of the balance between protein breakdown and protein synthesis. It has been shown that multiple conditions of muscle atrophy are characterized by the common regulation of a specific set of genes, termed atrogenes. It is not known whether various models of muscle hypertrophy are similarly regulated by a common transcriptional program. Here, we characterized gene expression changes in three different conditions of muscle growth, examining each condition during acute and chronic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…Importantly, this phenomenon is different from aging-related sarcopenia and sciatic denervation-induced atrophy, where the skeletal muscle total RNA concentration is not decreased (31,65). Also, our data show that ribosomal alterations in muscle atrophy are not necessarily the reverse of hypertrophy, because the changes in hypertrophy are believed to be due to translational rather than transcriptional perturbations (27). Interestingly, our observations using polysome profiling show that hyperammonemia does not seem to affect the proper maturation and assembly of the ribosomes.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Importantly, this phenomenon is different from aging-related sarcopenia and sciatic denervation-induced atrophy, where the skeletal muscle total RNA concentration is not decreased (31,65). Also, our data show that ribosomal alterations in muscle atrophy are not necessarily the reverse of hypertrophy, because the changes in hypertrophy are believed to be due to translational rather than transcriptional perturbations (27). Interestingly, our observations using polysome profiling show that hyperammonemia does not seem to affect the proper maturation and assembly of the ribosomes.…”
Section: Discussioncontrasting
confidence: 61%
“…While there is fairly robust evidence supporting a regulatory role of the ␤-catenin-cMYC axis in increased ribosomal biogenesis and translational changes during skeletal muscle hypertrophy (4)(5)(6)27), there are limited data as to whether decreased ribosomal biogenesis occurs during muscle atrophy. Ribosomal abundance, measured by total RNA quantity, and molecular regulators of ribosomal biogenesis were decreased in type II fibers in aged rats with muscle loss despite an increase in cMYC expression (28).…”
mentioning
confidence: 99%
“…21 As for transcriptional regulation of myofibrillar genes, recent work has linked increased muscle loading during synergist ablation of mouse extensor digitorum longus (EDL) muscles to transcriptional activity of serum response factor (SRF) and further to increased expression of myocellular genes, including several myofibrillar and immediate-early genes such as FOS and JUN. 22 In this regard, SRF transcriptional activity has been proposed to play an important role in the regulation of muscle mass, as evidenced by loss of overload-induced hypertrophy following inducible targeted deletion of skeletal muscle SRF in mouse. 23 However, with traditional physiological models of functional overload, changes in loading-induced tension development most likely also reflect changes in neural activation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, inhibition of mTORC1 seems to prevent an increase in protein synthesis following synergist ablation in rodents 17‐19 as well as following resistance exercise in rodents 20 and humans 21 . As for transcriptional regulation of myofibrillar genes, recent work has linked increased muscle loading during synergist ablation of mouse extensor digitorum longus (EDL) muscles to transcriptional activity of serum response factor (SRF) and further to increased expression of myocellular genes, including several myofibrillar and immediate‐early genes such as FOS and JUN 22 . In this regard, SRF transcriptional activity has been proposed to play an important role in the regulation of muscle mass, as evidenced by loss of overload‐induced hypertrophy following inducible targeted deletion of skeletal muscle SRF in mouse 23 …”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies addressing mTORC1 signalling in skeletal muscle have used pharmacological inhibition by treating mice with its specific inhibitor rapamycin. For example, different models of muscle hypertrophy are characterized by an increase in mTOR signalling and show a significant reduction or even complete ablation of muscle growth when administering rapamycin. We recently showed that this inhibitory effect of rapamycin in skeletal muscle is due to the inhibition of the two best defined mTORC1 targets: S6K1 and 4E‐BP1 .…”
Section: Introductionmentioning
confidence: 99%